Design and application of the recyclable poly(l-proline-co-piperidine) catalyst for the synthesis of mesityl oxide from acetone1. Issue 52 (10th June 2015) - Xu, Lin; Huang, Jiejun; Liu, Yubing; Wang, Yining; Xu, Bolian; Ding, Kehong; Ding, Yuanhua; Xu, Qing; Yu, Lei; Fan, Yining
<x xml:space="preserve">Abstract</x> A novel bi-component poly(l-proline-co-piperidine) catalyst was developed for the synthesis of mesityl oxide from acetone. The catalyst is more eco-friendly than traditional inorganic bases, avoiding the generation of corrosive solid, and the catalytic mechanism was studied.